Corpses, Fire, and Dangerous Mammals: Revisiting the Symbols in Roddam’s Television Adaptation of 'Moby Dick' by Herman Melville - Ricardo Sobreira (Anglo Saxonica, 2021)
This paper aims at discussing the visual symbols as well as aspects such as the acting performances, the historical accuracy, the teleplay, and the direction in Franc Roddam’s 1998 television miniseries 'Moby Dick', adapted from Herman Melville’s homonymous novel (1851). The two-part television production incorporates a few symbolic elements not necessarily present in the source text. These symbols (the image of a dog, the evocation of a giant, a whale-shaped mark, a great fire and an underwater corpse) are visually associated with characters as diverse as Elijah, Ahab, Queequeg and Moby Dick. The investigation focuses thus on the possible interpretations suggested by these visual symbols and how they contribute to better our comprehension not only of these characters but also of the novel’s complex themes of death, power, evil, redemption, among others.   Resumo O presente trabalho objetiva discutir os símbolos visuais bem como aspetos tais como as atuações, a reconstituição de época, a roteirização e a realização relativamente à minissérie de televisão 'Moby Dick' (1998), uma adaptação da obra homónima de Herman Melville, realizada por Franc Roddam. A produção televisiva, dividida em dois episódios, incorpora certos elementos simbólicos não necessariamente presentes no texto-fonte. Esses símbolos (a imagem de um cão, a evocação de um gigante, uma marca em forma de baleia, um incêndio de grandes proporções e um cadáver submerso) são visualmente associados a personagens tão diversas quanto Elijah, Ahab, Queequeg e Moby Dick. A investigação enfoca, portanto, as possíveis interpretações sugeridas por esses símbolos visuais e como eles contribuem para aprimorar a nossa compreensão de tais personagens e de temas complexos abordados no romance como a morte, o poder, o mal, a redenção, entre outros.   Palavras-Chave:  Estudos da Adaptação; Literatura Americana; Herman Melville; Moby Dick; Símbolo